Ilmu Hubungan Internasional Fakultas Ilmu Sosial Dan Ilmu Politik, Universitas Hasanuddin - Gusmawan, Aditya Dwi; Nugraha, Imam Fadhil (Media Hukum Indonesia (MHI), 2025)
This thesis analyzes the United States' strategy in diplomacy during the case of India-Pakistan conflict escalation in May 2025. In that month, the Kashmir region experienced an increase in violence after a terrorist attack that killed 26 civilians. President Trump claimed that U.S. mediation dictated the ceasefire agreement, but India denied this, assuring that the settlement was reached by the Indian and Pakistani states themselves. This study uses qualitative case study methodology and content analysis to explore the diplomatic practices of the United States using the frameworks of Practice Theory and Strategic Narrative Theory. The framework guides the following study findings: United States diplomacy in this case serves to enhance conflict resolution as it is a social practice of knowledge that serves to reinforce political meanings and activities. Practice Theory proves that the United States' diplomatic actions are integrated practices that maintain America's political position in South Asia. Strategic Narrative Theory shows how the United States constructed itself as an irreplaceable neutral mediator, using strategic narratives to legitimize its initiatives and maintain its geopolitical relevance in the face of Chinese and Russian intransigence. Whereas this analysis finds that the United States' diplomatic strategy operates in both instrumental and performative dimensions, claims of successful mediation serve interests in short-term conflict management and long-term hegemonic influence. Through this strategic narrative, the United States has a symbolic construction of dependency, where regional conflicts seem to require intervention from Washington; this model reinforces America's global centrality in the security architecture.